Counter-memories in Iranian cinema - Wittmann, Matthias, 1975-; Holl, Ute (Edinburgh : Edinburgh University Press Ltd, 2021)
"Farīd ad-Dīn-e ʻAṭṭār's Persian folk tale The Conference of the Birds relates the quest by thousands of pilgrim birds for an ideal king, the mythical bird called Sīmorgh. At the end of the quest, the surviving birds recognise that the longed-for king is nothing other than the reflection of their own existence. But what about those other birds that were not able to become part of the final representation? This groundbreaking book calls them 'counter-memories'; memories that are barred from hegemonic history, but are, nevertheless present in cinematic forms. Due to the strategic and artistic interventions of a range of Iranian filmmakers, such as Abbas Kiarostami and Shahram Mokri, Ali Hatami and Tahmineh Milani, Kianoush Ayari and Rakshan Banietemad, the history of post-revolutionary Iranian Cinema is also structured by counter-memories, with the potential to destabilise officially fabricated success stories of revolution, war and sacred defence. Counter-Memories in Iranian Cinema establishes a new framework for understanding the tensions between censorship and resistance, helping to carve out resistant points of remembering both within and outside state-controlled cinema."--Publisher description.
Introduction -- PART I AN ARCHAEOLOGY OF POSSIBLE FUTURES -- 1. The Incomplete: Film, Politics, and Remembering the Past / Tara Najd Ahmadi -- 2. The Hidden Half, or the Temporal and Collective Politics of Counter-Memory / Sara Saljoughi -- 3. Counter-Investigations: On Matchboxes, Black Boxes, and other Forgotten Futures / Chowra Makaremi and Emmanuel Alloa -- PART II MATERIAL MATTERS: MEMORY, ACCESSIBILITY, TRANSLATION -- 4. An Archaeology of Access: Materiality, Historiography, and Iranian Cinema / Blake Atwood-- 5. Black Seals: Missive from Iran's National Music / Negar Mottahedeh-- 6. Different Time, Different Space: Filmic Forms of Counter-Memory in Abbas Kiarostami's Koker Trilogy / Ute Holl -- PART III INTERSTICES. NICHES. IMPURE MEMORIES -- 7. Towards an Impure Memory: An Archaeology of Counter-Memories through Telescoping Lenses / Matthias Wittmann-- 8. Seeking Love in the Interstices: Acousmatic Listening as Counter-Memory in Abbas Kiarostami's Shirin (2008) / Michelle Langford -- 9. Spiritual Counter-Memories of the War: Mohammad Ali Ahangar's Recent Contributions to the Sīnemā-ye Defāʻ-ye Moqaddas / Viktor Ullmann -- PART IV TRANSGENERATIONAL GAPS AND TRANSMISSIONS -- 10. Filmfarsi as Counter-Memory / Pedram Partovi -- 11. A Shadow for Invisible Films: A Way to Break the Monopoly of Image Production in Iran / Shahram Mokri -- 12. 'At the End of a Century' (1996) / Bahram Beyzaie ; translated by Amir Roshan -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 01, 2023).
eBooks on EBSCOhost
Keywords: Motion pictures -- Iran -- History -- 20th century; Motion pictures -- Iran -- History -- 21st century; Memory in motion pictures; Iran -- History -- Revolution, 1979.; Cinéma -- Iran -- Histoire -- 20e siècle.; Cinéma -- Iran -- Histoire -- 21e siècle.; Mémoire au cinéma.; Iran -- Histoire -- 1979 (Révolution); Memory in motion pictures; Motion pictures; Iran; 1900-2099; History